Unraveling the Interplay Between Motivation and Self-Regulated Learning in Learning Statistics: A Case of Higher Education Institutions in Papua - Wangguway, Yustinus; Mandala, Arif Sapta; Ugadje, Evelien Fitri (LPPM Undiksha, 2025)
Many students have difficulty learning statistics, especially if they do not have a strong mathematical foundation. This study aims to analyze the influence of learning motivation and self-regulated learning (SRL) on statistics learning outcomes. The study was conducted using a quantitative approach on 50 fourth-semester students of the Early Childhood Education study program at a university in Papua, Indonesia. Data were collected through valid and reliable motivation and SRL questionnaires. The results showed that, separately, motivation and SRL did not have a significant effect on learning outcomes. However, simultaneously, both variables had a significant effect on learning outcomes. However, when combined, both significantly affected student learning outcomes, indicating that students with high motivation tended to have better SRL. These findings emphasize the importance of integrating motivational support with developing SRL strategies to improve academic achievement in statistics learning. Therefore, educational interventions that encourage motivation while strengthening SRL abilities can be an effective solution in helping students face challenges in learning statistics. Further research is suggested to explore mediating or moderating variables such as learning styles, emotional intelligence, and social support that may enrich understanding of the dynamics between motivation, SRL, and learning outcomes in various educational contexts.